PENGARUH KUALITAS PRODUK DAN ASOSIASI MEREK TERHADAP PENGARUH KUALITAS PRODUK DAN ASOSIASI MEREK TERHADAP KEPUTUSAN PEMBELIAN ULANG KONSUMEN BIORE BODY FOAM PADA MAHASISWI UNIVERSITAS NEGERI PADANG - Dwi Nanda Putri Sirajudin; Firman Firman (Jurnal Praktik Bisnis, 2015)
This research aims to analyze the effect of Product Quality and Brand Association Toward Repurchase Decision of Biore Body Foam to female students in Universitas Negeri Padang. This study held in Universitas Negeri Padang. Population of this research is all female students in Universitas Negeri Padang who has bought Biore Body Foam before. Sample has taken through Accidental Sampling with total samples 100 respondents. Data Analyzed are by using path analysis through SPSS version 16.00. The result of this research show that : (1) Product Quality has significant effect toward Brand Association of Biore Body Foam to female students in Universitas Negeri Padang, (2) Product Quality has significant effect toward Repurchase Decision Biore Body Foam to female students in Universitas Negeri Padang, (3) Brand Association has significant effect toward Repurchase Decision of Biore Body Foam to female students in Universitas Negeri Padang. Key Words: Product Quality, Brand Association, Repurchase Decision